Chiral Synthons by Enantioselective Hydrolysis of meso-Diesters with Pig Liver Esterase: Substrate-Stereoselectivity Relationships - Kunitomo Adachi; Susumu Kobayashi; Masaji Ohno (CHIMIA)
The enantioselective synthesis of some antibiotics by combination of enzymatic and non-enzymatic procedures brought us to look at the substrate-stereoselectivity relationships in more detail. The enantiomeric excess of the chiral half-esters (Scheme 1), and even the absolute configuration of these products have been found to vary in response to small structural changes in the substrates. The present study on the substrate-stereoselectivity relationships will be useful for the rational application of pig liver esterase (PLE) in the preparation of chiral building blocks.